1998
DOI: 10.1073/pnas.95.26.15481
|View full text |Cite
|
Sign up to set email alerts
|

rexB of bacteriophage λ is an anti-cell death gene

Abstract: In Escherichia coli, programmed cell death is mediated through ''addiction modules'' consisting of two genes; the product of one gene is long-lived and toxic, whereas the product of the other is short-lived and antagonizes the toxic effect. Here we show that the product of rexB, one of the few genes expressed in the lysogenic state of bacteriophage , prevents cell death directed by each of two addiction modules, phd-doc of plasmid prophage P1 and the rel mazEF of E. coli, which is induced by the signal molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 37 publications
8
100
0
Order By: Relevance
“…While this controversy can never distinctly be resolved for past events, it seems that in the Rex system, rexB may have originally been favoured because it protects E. coli from the killing mediated by addiction modules [37]. In combination with the sensor RexA, which is triggered by several unrelated phages [38], the system may have subsequently been coopted into an adaptive suicidal host-defence mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…While this controversy can never distinctly be resolved for past events, it seems that in the Rex system, rexB may have originally been favoured because it protects E. coli from the killing mediated by addiction modules [37]. In combination with the sensor RexA, which is triggered by several unrelated phages [38], the system may have subsequently been coopted into an adaptive suicidal host-defence mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratory experiments have demonstrated that this type of competition can influence the outcome of plasmid and virus evolution (Bull & Molineaux 1992;Turner & Chao 1998). Moreover, findings of antagonistic interactions between horizontally transmitted elements suggest that within-host competition plays an important role in their evolution in natural environments (Molineux & Spence 1984;Pecota & Wood 1996;Engelberg-Kulka et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…(1) The artificial overproduction of guanosine 3Ј,5Ј-bispyrophosphate (ppGpp) (Aizenman et al, 1996;Engelberg-Kulka et al, 1998), the amino acid starvation signal molecule produced by the RelA protein (Cashel et al, 1996), triggers death; (2) several antibiotics (rifampicin, chloramphenicol and spectinomycin) that are general inhibitors of transcription and/or translation trigger mazEF-mediated death Engelberg-Kulka et al, 2002); (3) Doc protein, which is the toxic product of the addiction module phd-doc of plasmid prophage P1 and is a general inhibitor of translation, drives post-segregational killing that requires the E. coli mazEF system ; (4) mazEFmediated cell death is triggered by DNA damage caused by thymine starvation (Sat et al, 2003), mitomycin C, nalidixic acid and UV irradiation ; (5) oxidative stress (H 2 O 2 ) and high temperature (50°C) also trigger mazEFmediated death.…”
Section: Mazef Is a Stress-induced Suicide Modulementioning
confidence: 99%